History and Literature: New Readings of Jewish Texts in Honor of Arnold J. Band - Jacobson, David C.; Cutter, William; Band, Arnold J. (Brown Judaic studies, 2020)
This collection of close textual reading by scholars in a variety of areas, including rabbinics, Jewish history, education, Hebrew literature, Yidish literature, America Jewish literature, is a tribute to Arnold Band. Each Essay constitutes a new and original reading of a text. The texts analyzed are drawn from a wide range of genres: talmudic legal texts, hasidic tales, folklore, as well as modern poems, essays, and works of fiction in Hebrew, Yiddish, German and English